Application of Nanomaterials in Food Industry and Agriculture - Pintér-Móricz, Ákos; Zákányiné Mészáros, Renáta (International Journal of Engineering and Management Sciences, 2022)
Nanomaterials have unique application features which can mainly be associated with their size properties. These materials have much higher surface than the normal particle size variant of the same materials. Due to these properties, nanomaterials are widely used in the industry. Food industry and the agrarian sector are using these materials increasingly. The main goal of nano size components and additives are the improvement of some parameters of the food manufacturing process, the elongation of the best before date of the food and the improvement of the texture, stability and the consistence of the food. Probably, nanomaterials will play an important role in the development of the food industry, moreover, it can be anticipated that nanotechnology will also appear there and will influence the whole food chain. It should be noted that food industry is using several nano size class materials which are not referred to as nanomaterials. Some examples are the micelles of some proteins, like milk protein, and fatty acids. Considering all these, the aim of our work was to present a thorough review and summary of the current applications.